2023
DOI: 10.1245/s10434-023-13679-x
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Oncological Outcome of Patients with Distal Femoral Osteosarcoma Managed by Limb Salvage Using Modular Endoprosthesis

Abstract: Background The aim of the study was to assess the functional and oncological outcomes of patients with distal femoral osteosarcoma managed by limb salvage using modular endoprosthesis as well as to assess related complications. Patients and Methods A total of 82 patients were included in our study. Functional outcome was assessed using MSTS score and knee range of motion. Oncological outcome was assessed regarding local recurrence, chest metastasis, and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…The overall LRR was 9.28%, and the LRR in the limb-salvage group (12.34%) was significantly higher than that of the amputation group (2.73%). Other long-term follow-up studies have reported local relapse rates between 3% and 10% in limb-salvage 16 19 . Local recurrence in osteosarcoma is directly associated with the margins of excision and with the responsiveness of the primary tumor to chemotherapy 5 .…”
Section: Discussionmentioning
confidence: 93%
“…The overall LRR was 9.28%, and the LRR in the limb-salvage group (12.34%) was significantly higher than that of the amputation group (2.73%). Other long-term follow-up studies have reported local relapse rates between 3% and 10% in limb-salvage 16 19 . Local recurrence in osteosarcoma is directly associated with the margins of excision and with the responsiveness of the primary tumor to chemotherapy 5 .…”
Section: Discussionmentioning
confidence: 93%
“…Malignant bone tumors preferentially develop at the metaphyses that surround the knee joint, and surgery usually involves the removal of the entire metaphysis followed by reconstruction. Currently, the most common surgical approach is reconstruction of the resected bone defect and contralateral articular surface using an endoprosthesis [ 1 , 2 ]. However, for some patients, if tumor resection is performed based on preoperative imaging assessment, it is possible to obtain a safe surgical margin while preserving the articular surface, resulting in greater postoperative function.…”
Section: Introductionmentioning
confidence: 99%